Peningkatan Kinerja Pasar Perusahaan Manufaktur Indonesia dan Malaysia: Peran Kualitas Laba - Arif Wahyu Nur Kholid; Rupianna Tambunan; Nistri Kusumawardani (Jurnal Penelitian Ekonomi Akuntansi, 2026)
This study aims to examine the effect of interest coverage and inventory management on the market performance of manufacturing companies in Indonesia and Malaysia, as well as to analyze the moderating role of earnings quality. This research applies a quantitative approach using secondary data from manufacturing companies listed on the Indonesia Stock Exchange and Bursa Malaysia in 2024. The sample consists of 574 companies selected through purposive sampling. The data were analyzed using multiple linear regression and Moderated Regression Analysis (MRA) with EViews 13. The results show that interest coverage has a positive and significant effect on market performance, while inventory management has no significant effect. Furthermore, earnings quality strengthens the effect of interest coverage on market performance but does not moderate the relationship between inventory management and market performance. These findings indicate that financial signals are more valuable to investors when supported by credible earnings quality. This study contributes to the development of signaling theory in the context of manufacturing companies in emerging markets.